English Teachers’ Gender Based Teaching Strategies in Teaching Descriptive Text - Setia Ningsih, Baiq Indria; Thohir, Lalu; Suryaningsih, Hartati; Arifuddin, Arifuddin (Jurnal Ilmiah Profesi Pendidikan, 2025)
Writing is one of the most essential and challenging skills in English language learning because it demands creativity, organization, and linguistic accuracy. Among various text types, descriptive text plays a crucial role in helping students express ideas clearly and vividly by describing people, places, or objects in detail. However, many students still face difficulties in generating ideas, organizing sentences, and using appropriate vocabulary. This study aimed to analyze gender based teaching strategies employed by male and female English teachers in teaching descriptive text and how these strategies are implemented in the classroom. The study employed a qualitative descriptive method. The participants were five English teachers at MTsN 1 Lombok Tengah, consisting of three males and two females. The data were collected through classroom observation and interviews and analyzed using data reduction, data display, and conclusion drawing. The results revealed that each teacher applied distinct strategies. Male teachers used guided writing, imaginary strategy, and visual learning to stimulate creativity and provide structural support, while female teachers used modified vocabulary instruction and collaborative learning to strengthen linguistic readiness and promote peer interaction. Drawing on the findings, it can be concluded that although male and female English teachers demonstrated different emphases in their teaching, both aimed to facilitate students’ descriptive writing development, boost confidence, and encourage active participation through supportive and interactive learning environments.